A new type of microscope illumination and its use in microbiology - Zizka, Z; Hostounský, Z (Folia microbiologica, 2006)
To overcome problems with taking photographs of motile microorganisms we used a new type of microscope illumination by means of a light-emitting diode (LED), which fully preserves the Kohler illumination principle. Oblique illumination or relief contrast after the Hostounsk, microscopy method were used for observing and photographing bacteria, flagellates and infusorians having different motion velocities with sufficient image contrast. The device, which permitted us to use short shutter time (1/30, 1/60 or 1/125 s), was successfully used in recording different motile microorganisms including their internal architecture.
Keywords: Animals; mikrofotografie; zvířata; mikroskopie; Bacteria; Ciliophora; Photomicrography; Microscopy; Eukaryota